Study on the Thermal State of a Transverse-Flux Motor - Andrii Yehorov; Oleksii Duniev; Andrii Masliennikov; Rupert Gouws; Oleksandr Dobzhanskyi; Mario Stamann (IEEE Access)
Based on the analysis of transverse flux machine designs, it was established that they exhibit a relative simplicity of design and demonstrate high specific power indices. This paper seeks to explore the influence of design features on the heating of the stator coil, identified as the most temperature-sensitive element in the system. Additionally, the study aims to characterize the temperature distribution pattern within the stator. To achieve this goal, experiments were conducted using a 3D model of a low-speed transverse flux motor. Thermal analysis was carried out using modern software, enabling the determination of temperature patterns in the coil, cores, and stator body. Graphs illustrating the temperature rise over time for each motor component were generated. The obtained results include corresponding graphs and dependencies, revealing that the average coil temperature reached 92°C, deviating by 3.3% from the experimental value. A significant finding is that the stator coil in a transverse flux motor experiences non-uniform heating, with temperature variations in areas lacking circulated air. Introducing thermal paste in the region enclosed by the U-shaped cores, coil, and body was found to equalize and reduce the stator coil temperature by 10%. These modeling results were subsequently validated through experimentation on the operational prototype of the TFM-200/32 transverse flux motor.